Dialektika Islam Politik dan Nasionalisme: Analisis Restrospektif - Zuhri Humaidi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
One important issue in state politics is how to put political Islam in the context of a multicultural Indonesian. This problem has become a fundamental problem since the republic was founded, and for some people remain a stumbling block in the nation project building up to now. With a Historical-Sociological approach, this paper rejects a number of arguments counter-Islamism. When Syarikat Islam was founded in 1912, the idea of ​​nationality extends beyond the boundaries of ethnicity and regionalism. SI (Syarekat Islam) is the first political party so that it becomes an exercise not only for trips of Political Islam, but for the development of national politics. Political Islam suffered great pressure on the era Orde Baru, but after the Orde Baru Era, political Islam re-emerged in a new articulation. A phenomenon mentioned by Asef Bayat as Post-Islamism, that is the party (group) Muslims behave realistically and pragmatically willing to follow the democratic process and ignore the purely ideological schemes. Islamic parties, such as PKB, PPP, PKS, the United Nations, and others that carries almost no issues like Islamic state, the Jakarta Charter, Islamic ideology, the application of sharia, etc., the rest were more on the more secular and pragmatic. Climate democratization runs while opening the possibility for erosion of the tendency of radicalism and extra-constitutional movement of political Islam.